Isolated Nasal Tip Metastasis from Esophageal Squamous Cell Carcinoma: Case Report and Literature Review - Ledderose, Georg J. (Case Rep Otolaryngol, 2015)
Objectives. Cutaneous metastases can be the first sign of a malignant disease and have an unfavorable prognostic significance. The external nose is rarely affected. The uncommon clinical presentation of these cutaneous metastases may lead to the wrong diagnosis and treatment. Methods. We present the case of a 59-year-old patient with a small indolent tumor on the tip of the nose that turned out to be the first sign of an extended esophageal cancer. Conclusion. The differential diagnosis of tumors of the facial skin and the nasal tip includes metastases from an unknown primary tumor. In rare cases, squamous cell carcinoma of the esophagus needs to be considered.